Newer drugs for the treatment of hepatitis B viral infection - Venugopal, Sreelakshmi; Harichandran, Dhanya Thirookaran; SanalKumar, K. B.; Sujatha, M. B. (International Journal of Basic & Clinical Pharmacology, 2020)
One of the main disadvantages of hepatitis B virus treatment is the persistence of the virus even after treatment. The main causes of this viral persistence can be an inadequacy of the immune function as well as some viral factors. The currently available drugs for hepatitis B are five oral nucleoside/nucleotide analogs (lamivudine, adefovir dipivoxil, tenofovir, entecavir, telbivudine) and two interferon drugs (interferon alfa-2b, pegylated interferon alfa-2a). However, these therapies do not lead to sustained remission, requiring indefinite treatment as viral load frequently rebounds once suppressive therapy is stopped.